Evaluation of Posterior Cruciate Ligament and Intercondylar Notch in Subjects With Anterior Cruciate Ligament Tear: A Comparative Flexed-Knee 3D Magnetic Resonance Imaging Study - Taneja, Atul K.; Miranda, Frederico C.; Demange, Marco K.; Prado, Marcelo P.; Santos, Durval C.B.; Rosemberg, Laercio A.; Baroni, Ronaldo H. (Arthroscopy, 2018)
To determine if posterior cruciate ligament (PCL) and intercondylar notch (IN) morphometries and volumetrics act as risk factors for anterior cruciate ligament (ACL) tears. A prospective case-controlled magnetic resonance imaging (MRI) study was conducted with subjects presenting noncontact knee injuries. Exclusion criteria were previous surgery, PCL tear, osteoarthritis, tumors, or infectious and inflammatory conditions. All participants underwent a flexed-knee 3-dimensional (3D) magnetic resonance imaging (MRI) to uniformly straighten PCL. MR images were independently reviewed by 2 radiologists and assessed for 2D and 3D measurements (bicondylar width; IN angle, depth, width, and cross-sectional area; PCL width, thickness, and cross-sectional area; and IN and PCL volumes). Clinical profiles were tabulated and subjects were divided into cases (ACL tear) and controls (without ACL tear). The study was composed of 50 cases versus 52 controls (N = 102), with a mean age of 36.8 years. There was no difference between groups (P > .05) regarding age, gender, body mass index, time from injury, Tegner score, flexion angle, limb side, intensity of injury, or familial or opposite limb history of tear. Agreement between readers ranged from substantial to almost perfect. Subjects with ACL tear presented with lower IN width, lower IN minus PCL widths, lower Notch Width Index, higher PCL/IN width proportion, higher PCL thickness, lower IN depth minus PCL thickness, and higher PCL thickness/IN depth proportion (P < .05). Moreover, higher PCL/IN cross-sectional area proportion, higher PCL volumes (OR = 9.01), and higher PCL/IN volume proportion were also found in cases. Our study shows that subjects with ACL tears present not only reduced IN but also larger PCL dimensions. These findings, isolated and combined, and especially PCL volume, might be suggestive as risk factors for ACL tears owing to the reduction of its space inside the IN. Level III, comparative group.